Comparative analysis of psychophysiological features of taekwondo athletes of different age groups - Leonid Podrigalo; Vyacheslav Romanenko; Olha Podrihalo; Sergii Iermakov; Anatolyi Huba; Volodymyr Perevoznyk; Olexandr Podavalenko (IP Iermakov S.S., 2023)
Background and Study Aim. The importance of psychophysiological features in optimizing the functional state of athletes is beyond doubt. The aim of this study was a comparative analysis of the psychophysiological features of taekwondo athletes of different age groups. Material and Methods. The study involved 42 taekwondo athletes, skill level 2 Gup - 1 Dan. The participants were divided into groups of 14 people. Group 1 - (7.50±0.14) years, Group 2 - (10.07±0.22) years, Group 3 - (13.36±0.27) years. A special computer program for devices with the iOS operating system was used. The Apple iPad, 4th generation with a screen diagonal of 9.7 inches was used. The following tests were used: reaction choice (RC), reaction to a moving object (RMO) and size test (ST). The results of the groups were compared using the nonparametric Rosenbaum test (Q), and the Pearson correlation coefficient (r) was determined. Results. RMO test results in group 2 were significantly better than those in group 1 (Q=12, p<0.01). A similar correlation was determined for RC (Q=14, p<0.01) and ST (Q=15, p<0.01). When analyzing the frequency of incorrect reactions in RMO, it was found that athletes in the 1st group lagged behind more often (Q=6, p<0.05). A comparison of groups 2 and 3 confirmed that senior athletes had better results in RC (Q=11, p<0.01). For all tests used, the best results of group 3 compared with group 1 was determined: for RMO Q=16, (p<0.01), for RC Q=22, (p<0.01), for ST Q=20, (p<0.01). Senior athletes often had an anticipatory reaction in RMO, (Q=7, p<0.05). Significant correlations (p<0.05) were determined in group 1 between age and frequencies of anticipatory (r=-0.57) and lagging reactions (r=0.57), RMO and RC (r=0.63), RC and frequencies of anticipatory reactions (r=0.57) and lagging reactions (r=-0.57). In group 3, significant correlations were determined between age and RC (r=-0.59), RMO and RC (r=0.76), age and ST (r=-0.53), RMO and ST (r=0.65), RC and ST (r =0.79).  Conclusions. A change in the speed of reaction to various stimuli of taekwondo athletes of different ages has been confirmed. An increase in age and training experience improves the reaction rate. This dependence is most pronounced when comparing junior and senior athletes. The determined correlations between all tests used also reflect the improvement in the psychophysiological state of the athletes with increasing age. The tests used are characterized by accessibility, specificity, informativeness and financial feasibility. The results obtained allow for recommending their use in monitoring the state of martial arts athletes.